2021
DOI: 10.1111/trf.16284
|View full text |Cite
|
Sign up to set email alerts
|

Effects of red blood cell transfusion on global oxygenation in anemic critically ill patients

Abstract: Background Consensus for transfusion in intensive care unit (ICU) patients recommends a restrictive strategy, based on a hemoglobin (Hb) concentration of 7 g/dL. Red blood cell (RBC) transfusion is used to prevent tissue hypoxia by improving oxygen transport (DO2) and therefore oxygen consumption (VO2). We studied the effects of RBC transfusion on systemic oxygenation parameters reflecting systemic oxygen extraction (EO2 = DO2/VO2): S(c)vO2, lactate level, venous‐to‐arterial carbon dioxide difference (Pv‐aCO2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
(63 reference statements)
1
7
0
2
Order By: Relevance
“…In our study we analysed only RBCT with elevated (≥1.8 mmol/L) pre-transfusion lactate in order to show the effect of RBCT on its concentration. Normal (<1.8 mmol/L) lactate does not decrease further following RBCT, as was shown in the study by Themelin et al [15]. Themelin showed that even with normal pre-RBCT lactate, ScvO 2 improved significantly following RBCT, showing that lactate does not have appropriate sensitivity as a physiologic RBCT trigger.…”
Section: Discussionmentioning
confidence: 70%
“…In our study we analysed only RBCT with elevated (≥1.8 mmol/L) pre-transfusion lactate in order to show the effect of RBCT on its concentration. Normal (<1.8 mmol/L) lactate does not decrease further following RBCT, as was shown in the study by Themelin et al [15]. Themelin showed that even with normal pre-RBCT lactate, ScvO 2 improved significantly following RBCT, showing that lactate does not have appropriate sensitivity as a physiologic RBCT trigger.…”
Section: Discussionmentioning
confidence: 70%
“…Therefore, multicenter, larger-sample studies are required in the future. Based on the finding that a relatively high MAP improved tissue perfusion during CPB, our future study will monitor the peripheral circulation during CPB by ultrasound and calculate oxygen supply and consumption for more convincing evidence [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Themelin et al deuten in einer Studie mit Intensivpatienten an, dass Transfusionen vor allem einen Effekt auf die zentralvenöse Sauerstoffsättigung hatten, wenn diese initial bei < 70 % lag [57]. Außerdem sollte die Kompensationsfähigkeit des Patienten bei der Transfusionsentscheidung mit einbezogen werden.…”
Section: Merkeunclassified